PELAKSANAAN DIVERSI DALAM PENYELESAIAN TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK SEBAGAI BENTUK PENDEKATAN RESTORATIVE JUSTICE (Studi di Wilayah Hukum Kepolisi an Resort Banjarnegara) - Triadi Agus Purwanto (Jurnal Idea Hukum, 2018)
This thesis is motivated by the problem of Children who are the assets of the nation, as part of the young generation of children plays a very strategic role as a successor of a nation. Therefore, the state must provide protection for children if the child becomes a criminal offender. One of the solutions that can be taken in handling the case of crime of theft committed by the Child is through Restorative Justice approach, which is implemented by diversion as regulated in Law Number 11 Year 2012 on Child Criminal Justice System. Banjarnegara Resort Police has implemented a version for handling of criminal cases of theft committed by the Child as an effort to settle the case. Based on this, the issue raised in this thesis is how the implementation of the diversion in the settlement of criminal acts of theft committed by the Children in the Legal District of Banjarnegara Police as a form of Restorative Justice approach and constraints in the implementation of such diversions.